The bookmark method to establish minimum performance standards for intensive care flight paramedics performing helicopter winch rescue. (February 2023) - Meadley, Ben; Rogers, Matthew; Bowles, Kelly-Ann; Caldwell, Joanne
Abstract: We aimed to use the bookmark method to establish minimum standards for selecting intensive care flight paramedics. Two subject matter expert (SME) focus groups reviewed nine videos of decreasing duration showing land and water helicopter rescue tasks. Focus Group 1 (FG1, n = 10) viewed videos individually off-site, whilst Focus Group 2 (FG2, n = 9) attended a face-to-face session. All SMEs selected the video they judged as the appropriate pace for the task then reviewed feedback. For both groups, the process was repeated until 80% agreement was achieved, or three rounds were completed (whichever occurred first). FG1 and FG2 achieved agreement after two rounds for the land task. For the water task, FG1 did not reach agreement. FG2 reached consensus after two rounds. The selected task durations were similar. The bookmark method is valuable to determine performance standards for performing winch rescue, and SMEs are more likely to reach consensus when face-to-face. Highlights: Online and face-to-face focus groups analysed videos of helicopter rescues. The aim was to set a cut score for performance standards in this profession. The groups used the bookmark method to select the minimum pace. The face-to-face focus group set a cut score in less rounds. Further research may enhance the reliability of the online method.